Dual-Beam Antenna Design for Autonomous Sensor Network Applications - Jean-Marie Floc'h; Ahmad El Sayed Ahmad; Yvan Kokar (International Journal of Antennas and Propagation)
This paper describes our contribution in the ANR project called CAPNET dedicated to the site security (autonomous sensor network). The network is autonomous in term of energy and it is very easy to deploy on the site (the time to deploy each node of the network is around 10 minutes). The first demonstrator was deployed in the fire base station of Brest, France with 10 nodes with a security perimeter around 1.5 km. Our contribution takes place in the field of antennas, with the development of two systems: a single-beam antenna reserved for the supervisor or the last node of the network, and a dual-beam antenna dedicated to the node in linear configuration. For the design and optimization of antennas, we use HFSS CAD software from ANSOFT. The antennas have been designed and successfully measured.